Evaluating the Effectiveness of Business plan Approach for First Time Entrepreneurs Case Study: IBE SBM ITB - Khoironi, Arizal; Herliana, Sri (Journal of Business and Management, 2015)
Abstract-This research is a preliminary research into finding out the best approach for first time entrepreneur to start their business. The main objective of this research is to evaluate the effectiveness of business plan approach for first time entrepreneur to reach a desire product/market fit by evaluating the outcome of IBE program. It is important to know if the approach that used in the IBE program can generate product market fit so it can be produce a good business plan and worthy funded. According to result of this research revealed that the approach used in the IBE programs have not been effective to find a product market fit for their business. The result of program evaluation with using CIPP Evaluation Model proves that still a lack of understanding of the market, resulting in strategy and business plan being developed inaccurate and many changes when execution. And at the end of the IBE program, it turns out they are also still not get the products that fit the market, resulting in most of them do not continue the business. So, it necessary to a renewed focus on IBE programs that better understanding of the market, so it can produce more effective business plan that will make it easier to execution and future business progression.Â Keywords: Business plan approach, product market fit, program evaluation